Highly degradable imine-doped mesoporous silica particles. (15th November 2018) - Travaglini, Leana; Picchetti, Pierre; Totovao, Ricardo; Prasetyanto, Eko Adi; De Cola, Luisa
Abstract : Enhanced degradation of mesoporous silica particles in neutral and acidic aqueous solutions was achieved by embedding diimine moieties in the silica network. Abstract : The degradation of mesoporous silica particles (MSPs) in water is a key aspect that boosts their use especially in bio-related fields. Although MSP degradation in aqueous media has been proven, big efforts have been devoted to tuning silica dissolution in order to obtain functional materials whose degradation can be finely controlled and enhanced, to tackle the issue of bioaccumulation. In particular, the introduction of stimuli-responsive functional groups into the silica framework was proven to be a successful strategy. Yet, the fast dissolution of silica particles in aqueous media in the absence of external stimuli has to be fully addressed. In this context, we reported herein the preparation and thorough characterisation of MSPs containing imine groups embedded within the silica framework (Im-MSPs ). Particles with different contents of imine groups have been investigated in order to assess the effect on the physicochemical properties and theIm-MSPs showed fast degradation in both acidic and neutral aqueous solutions, at a rate that depended on the pH value. Of special interest is their fast degradation at acidic pH, where instead MSPs are normally more stable. The described results unveil the potential of these particles in applications that require a fast degradation in aqueous media.